AN ANALYSIS OF MANAGEMENT OF FAMILY HOPE PROGRAM FOR POOR HOUSEHOLDS IN JAYAPURA MUNICIPALITY - Daryono Daryono; Meinarni Asnawi; Yundy Hafizrianda (Universitas Cenderawasih, 2016)
One of government policies to alleviate poverty was through a Family Hope (Keluarga Harapan) Program. This Family Hope Program delivered cash grants to poor households who met some certain conditions and criterion. This was to improve the well-being and education of Family Hope’s recipients and members of family. This study intends to review and analyse Planning, Budgeting, Implementation and Evaluation processes of Family Hope Program in the municipality of Jayapura. This Research used a descriptive statistics. The study found that the planning process of Family Hope Program was prepared by Government of Jayapura Social Work Unit. Also, the budget came from the central government through Ministry of Social Affairs. The Family Hope Program grants payment was made through Post Office in Jayapura. Meanwhile, the evaluation for Family Hope Program arranged Provincial Government through its Social Work Unit, the Ministry Of Social Affairs and National Development Planning Agency Key Words :Poverty, Family Hope Program, Prerequisite Cash Grants